A new and convenient synthetic way to 2-substituted thieno[2,3-b]indoles - Irgashev, Roman A.; Karmatsky, Arseny A.; Rusinov, Gennady L.; Charushin, Valery N. (Beilstein Journal of Organic Chemistry, 2015)
A short and robust approach for the synthesis of 2-(hetero)aryl substituted thieno[2,3-b]indoles from easily available 1-alkylisatins and acetylated (hetero)arenes has been advanced. The two-step procedure includes the “aldol-crotonic” type of condensation of the starting materials, followed by treatment of the intermediate 3-(2-oxo-2-(hetero)arylethylidene)indolin-2-ones with Lawesson’s reagent. The latter process involves two sequential reactions, namely reduction of the C=C ethylidene double bond of the intermediate indolin-2-ones followed by the Paal–Knorr cyclization, thus affording tricyclic thieno[2,3-b]indoles.
Keywords: aldol-crotonic condensation; isatin; Lawesson’s reagent; methyl ketones; Paal–Knorr reaction; thieno[2,3-b]indole